The impact of preoperative hip heterotopic ossification extent on recurrence in patients with head and spinal cord injury: a case control study. - François Genêt; Claire Jourdan; Christine Lautridou; Clément Chehensse; Kambiz Minooee; Philippe Denormandie; Alexis Schnitzler (PLoS ONE, 2011)
BACKGROUND: The preoperative Heterotopic Ossification (HO) extent is usually one of the main used criteria to predict the recurrence before excision. Brooker et al built a radiologic scale to assess this pre operative extent around the hip. The aim of this study is to investigate the relationship between the recurrence risk after hip HO excision in Traumatic Brain Injury (TBI) and Spinal Cord Injury (SCI) patients and the preoperative extent of HO. METHODOLOGY/PRINCIPAL FINDINGS: A case control study including TBI or SCI patients following surgery for troublesome hip HO with (case, n = 19) or without (control, n = 76) recurrence. Matching criteria were: sex, pathology (SCI or TBI) and age at the time of surgery (+/-4.5 years). For each etiology (TBI and SCI), the residual cognitive and functional status (Garland classification), the preoperative extent (Brooker status), the modified radiological and functional status (GCG-BD classification), HO localization, side, mean age at the CNS damage, mean delay for the first HO surgery, and for the case series, the mean operative delay for recurrence after the first surgical intervention were noted. CONCLUSIONS/SIGNIFICANCE: The median delay for first HO surgery was 38.6 months (range 4.5 to 414.5;) for the case subgroup and 17.6 months (range 5.7 to 339.6) for the control group. No significant link was found between recurrence and operative delay (p = 0.51); the location around the joint (0.07); the Brooker (p = 0.52) or GCG-BD status (p = 0.79). Including all the matching factors, no significant relationship was found between the recurrence HO risk and the preoperative extent of troublesome hip HO using Brooker status (OR = 1.56(95% CI: 0.47-5.19)) or GCG-BD status (OR class 3 versus 2 = 0.67(95% CI: 0.11-4.24) and OR class 4 versus 2 = 0.79(95%CI: 0.09-6.91)). Until the pathophysiology of HO development is understood, it will be difficult to create tools which can predict HO recurrence.